Bjerke_et_al_Nord_J_Bot_2018_Fig_2a - Bjerke, Jarle; Wierzbinski, Grzegorz; Tømmervik, Hans; Phoenix, Gareth; Bokhorst, Stef (Dryad Digital Repository, 2018)
Characteristics of shoots with wintergreen leaves measured ca. 5 days after snowmelt in early May 2015: Number of leaves and buds per shoot during May 2015.